Testing tribocorrosion of passivating materials supporting research and industrial innovation : handbook - Celis, Jean-Pierre; Ponthiaux, P. (Publications (European Federation of Corrosion), 2012)
This book is intended primarily for industrial laboratories and technical centres interested in standardised tests in the field of tribology and combined tribology-corrosion.